(1442) Crisis of compromise on some issues of international order and third world problems أزمة التوافق بشأن بعض قضايا النظام الدولي ومشاكل العالم الثالث - Moustafa, Moustafa Ahmed (The Institute of National Planning, 2018)
The subject of this paper is in fact a trial to reassess three related sub-subject to "international order" and third world. The first is concerning and entitled "peace and Arms.